Recent Advances for Drought Stress Tolerance in Maize (Zea mays L.): Present Status and Future Prospects - Sheoran, Seema; Kaur, Yashmeet; Kumar, Sushil; Shukla, Shanu; Rakshit, Sujay; Kumar, Ramesh (Frontiers in Plant Science, 2022)
Drought stress has severely hampered maize production, affecting the livelihood and economics of millions of people worldwide. In the future, as a result of climate change, unpredictable weather events will become more frequent hence the implementation of adaptive strategies will be inevitable. Through utilizing different genetic and breeding approaches, efforts are in progress to develop the drought tolerance in maize. The recent approaches of genomics-assisted breeding, transcriptomics, proteomics, transgenics and genome editing have fast-tracked enhancement for drought stress tolerance under laboratory and field conditions. Drought stress tolerance in maize could be considerably improved by combining omics technologies with novel breeding methods and high-throughput phenotyping. This review focuses on maize responses against drought, as well as novel breeding and system biology approaches applied to better understand drought tolerance mechanisms and the development of drought-tolerant maize cultivars. Researchers must disentangle the molecular and physiological bases of drought tolerance features in order to increase maize yield. Therefore, the integrated investments in field-based high-throughput phenotyping, system biology, and sophisticated breeding methodologies are expected to help increase and stabilize maize production in the face of climate change.